La Vida Buena (The Good Life) evaluation: a quasi experimental intervention of a community health worker-led family-based childhood obesity program for Latino children 5-8 years of age on the US-Mexico border - Kathryn M. Tucker; Maia Ingram; Kevin Doubleday; Rosie Piper; Scott C. Carvajal (BMC, 2019)
Abstract Background Due to multiple and interacting factors, Latino children are disproportionately at risk for overweight and obesity in the United States. Childhood obesity increases the risk for adverse physical and psychosocial outcomes throughout the lifespan. Intensive behavioral interventions recommended in primary care settings may not conform to current practices, and the most vulnerable populations are often unable to access these services. Community Health Workers (CHWs) offer a promising approach to bridging the gap between vulnerable communities and culturally competent services. La Vida Buena (The Good Life) is an 8-week family-focused intervention for Latino children 5-8 years old and their parents or caregivers who are patients at a Federally-Qualified Community Health Center (FQHC). It is a culturally and linguistically appropriate curriculum, facilitated by CHWs, that targets family behaviors to foster a healthy lifestyle in order to prevent and mitigate childhood overweight and obesity. Methods The primary objective is to test the effectiveness of the La Vida Buena (LVB) childhood obesity program among Latino children 5-8 years old and their families as compared with a single educational session. This study uses a parallel two-arm quasi-experimental design. The intervention group receives the 8-week La Vida Buena intervention and the comparison group receives a single educational session. The primary outcome is the change in the child's BMI z-score from baseline to 6 months. Discussion The implementation and evaluation of La Vida Buena may inform research and practice for linking Latino patients in FQHCs to culturally responsive community-based childhood obesity interventions. It will also contribute to the literature about CHWs as facilitators of behavior change for families underserved by health services and preventive programs. La Vida Buena can serve as a culturally and linguistically appropriate early intervention curriculum that will foster a healthy home environment for childhood obesity mitigation and prevention. Trial registration The trial was retrospectively registered on December 18, 2018. The ClinicalTrials.gov Identifier is NCT03781856.